Hearing the voices of students with autism. What is the lived experience of students in an ASD class? - Abraham, Lucy (2017)
The education of students with Autism Spectrum Disorder (ASD) has been subject to debate for a number of years, particularly following the international commitment to inclusive education. In Ireland students with ASD have access to a continuum of provision which affords them the opportunity to attend a mainstream school, a special school or a special class within a mainstream school. This study sought to obtain the voices of students with ASD in order to gain a more in depth understanding of their experiences in an ASD class within a mainstream school. Four students with ASD took part in this qualitative study, sharing their experiences through drawings, semi-structured interviews and photo-elicitation interviews. Interpretive phenomenological analysis was used to examine the data and the findings demonstrate their experiences are predominantly positive, furthermore it became apparent the participants viewed the school as a whole as having a positive influence on their experiences.